2021
DOI: 10.1186/s10194-021-01330-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory complications of CGRP monoclonal antibodies: a case series

Abstract: Background Calcitonin gene-related peptide (CGRP) is expressed throughout the body and is a known mediator of migraine, exerting this biological effect through activation of trigeminovascular, meningeal and associated neuronal pathways located in close proximity to the central nervous system. Monoclonal antibodies (mAb) targeting the CGRP pathway are an effective new preventive treatment for migraine, with a generally favourable adverse event profile. Pre-clinical evidence supports an anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…CGRP-targeting medication is effective in 50% of chronic and episodic migraine patients, but some recent studies have brought on concerns about potential immune effects. A series of 8 case studies from Australia and Ireland found potential immune complications from the CGRP antibodies erenumab or galcanezumab ( 142 ). Patients had complications such as a man who suffered from rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP-targeting medication is effective in 50% of chronic and episodic migraine patients, but some recent studies have brought on concerns about potential immune effects. A series of 8 case studies from Australia and Ireland found potential immune complications from the CGRP antibodies erenumab or galcanezumab ( 142 ). Patients had complications such as a man who suffered from rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The migraine animal model also induces an increase in circulating CGRP levels in plasma ( Cohen et al, 2021 ; Sun et al, 2021 ) and cerebrospinal fluid of the nestin/hRAMP1 transgenic mice ( Recober et al, 2009 ). Additionally, CGRP may trigger the release of pro-inflammatory cytokines ( Ray et al, 2021 ), particularly IL-6 and TNF-α, which are also increased in the plasm of migraine patients ( Yücel et al, 2016 ; Conti et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…CGRP may lead to the release of pro-inflammatory cytokines ( Ray et al, 2021 ), and the levels of interleukine-6 (IL-6) and tumor necrosis factor alpha (TNF-α) were increased in the plasm of migraine patients ( Ray et al, 2021 ). In fact, the application of IL-6 in the dura mater and cisterna magna causes both periorbital and hind paw cutaneous hypersensitivity ( Avona et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, one would postulate that anatomical separation between the hemispheres would occur, to give rise to the one-sidedness of migraine pain. CGRP even exerts anti-inflammatory properties in some tissue, questioning its role as a pro-inflammatory mediator and its safety as a systemic drug target, as blocking the anti-inflammatory properties could result in inflammation-related consequences elsewhere [ 150 ].…”
Section: Concluding On Cgrp and Inflammation—a Perspectivementioning
confidence: 99%